Penguatan Kompetensi Pedagogik Guru melalui Pelatihan Pembelajaran Inkuiri di Sanggar Bimbingan SIKL Malaysia - Sari, Dhita Ayu Permata; Erman, Erman; Budiyanto, Mohammad; Mursyidah, Roihana Waliyyul; Ilhami, Fasih Bintang; Sabtiawan, Wahyu Budi (Universitas Nusantara PGRI Kediri, 2026)
Quality education depends heavily on teachers' pedagogical competence. At Sanggar Bimbingan SIKL Malaysia, there is an urgent need to improve teachers' skills in implementing effective learning methods, particularly inquiry-based learning, in response to increasingly complex student learning challenges. This community service program involved a two-day inquiry-based learning training program, which included theory sessions, practical design sessions, and group discussions. Participants included 17 teachers currently working at Sanggar Bimbingan SIKL. Evaluation used tests to measure changes in their understanding and application of inquiry-based learning methods. The results of the activity showed that teachers were able to explore various sources of information to generate ideas for designing inquiry-based learning. Test results indicated that teachers' understanding and skills after the training were between 80 and 100. Furthermore, teachers responded positively to the training program, considering its content, usefulness, impact, motivation, and facilities and infrastructure. These findings demonstrate that the training was effective in positively impacting the pedagogical competence of Sanggar Bimbingan teachers.